2010
DOI: 10.5194/angeo-28-1013-2010
|View full text |Cite
|
Sign up to set email alerts
|

Source mechanism of Saturn narrowband emission

Abstract: Abstract. Narrowband emission (NB) is observed at Saturn centered near 5 kHz and 20 kHz and harmonics. This emission appears similar in many ways to Jovian kilometric narrowband emission observed at higher frequencies, and therefore may have a similar source mechanism. Source regions of NB near 20 kHz are believed to be located near density gradients in the inner magnetosphere and the emission appears to be correlated with the occurrence of large neutral plasma clouds observed in the Saturn magnetotail. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Z mode emission at Saturn is observed associated with narrowband emission as discussed by Ye et al [2010]. The clearest examples are the 5 kHz narrowband emission as shown in Figure 9, but Z mode is also associated with upper hybrid emission near strong density gradients and source regions of 20 kHz narrowband emission as discussed by Menietti et al [2009, 2010]. In Figure 9 narrowband emission near 5 kHz is seen both above and below f c .…”
Section: Saturn Chorus Observationsmentioning
confidence: 73%
“…Z mode emission at Saturn is observed associated with narrowband emission as discussed by Ye et al [2010]. The clearest examples are the 5 kHz narrowband emission as shown in Figure 9, but Z mode is also associated with upper hybrid emission near strong density gradients and source regions of 20 kHz narrowband emission as discussed by Menietti et al [2009, 2010]. In Figure 9 narrowband emission near 5 kHz is seen both above and below f c .…”
Section: Saturn Chorus Observationsmentioning
confidence: 73%
“…Computation of growth rate for Z mode waves by Menietti et al . [, , ] also indicated that Z mode waves have very large normal angles. In this study, we assume that the wave normal angle distribution of Z mode waves is Gaussian with a peak at 89°, which is described as follows [e.g., Glauert and Horne , ; Ni et al ., ]: gX={leftexp()XXmXw2XminXXmaxleft0otherwise,where X = tan( θ ) with θ as the wave normal angle, X m (=tan θ m ) is the peak, X w (=tan θ w ) is the angle width, and X min (=tan θ min ) and X max (=tan θ max ) are the lower and upper cutoff.…”
Section: Modelsmentioning
confidence: 99%
“…Although the energy source for the generation of the Z-mode waves is still unclear, linear growth rate calculations indicate that the observed plasma distributions are unstable to the growth of electrostatic cyclotron harmonic emission. Electromagnetic Z-mode could also be directly generated by the cyclotron maser instability Menietti et al, 2010]. (6) Similar to SKR, the 5 kHz NB emissions have a clock-like source and display two distinct modulation periods identical to the northern and southern hemisphere periods of SKR [Ye et al, 2010b].…”
Section: Resultsmentioning
confidence: 99%
“…f UH ∼ = nf ce Menietti et al, 2010]. These Z-mode waves can then mode convert to L-O mode on a density gradient or density irregularities.…”
Section: Source Mechanismmentioning
confidence: 99%